LAPAROSCOPIC CHROMOPERTUBATION FOR THE EVALUATION OF TUBAL PATENCY IN DAIRY CATTLE - SOFI, K A; SINGH, M; KUMAR, P; SHARMA, A (The Indian Journal of Animal Reproduction, 2022)
The present study was conducted to evaluate feasibility of laparoscopic chromopertubation using methyleneblue dye as a tubal patency test in bovines. This test was done during routine laparoscopic examination of dairycattle (n=5). Laparoscopy was done through left flank and blood / serum samples were collected for hematology,biochemical and hormone analysis at pre- (1 h) and post- (1 and 24 h) laparoscopic procedure. For evaluatingtubal patency, Foley’s catheter was inserted into the right uterine horn, fixed and about 30-40 ml autoclaveddilute methylene blue dye (2.5%) was then administered into the horn. The passage of dye through the fallopiantube was observed and appearance of blue color in the oviduct and spillage of dye through the fimbrial end wasindicative of patency. The same procedure was repeated on left uterine horn to determine patency. The procedurewas successfully done in four cattle and out of these, the left oviduct was blocked at utero-tubal junction onlyin one cattle. Pre- and post-laparoscopy, the hematological and serum enzyme parameters remained similar(p>0.05), however, serum cortisol was elevated at 1 h post-laparoscopy (p
Keywords: Bovines; Cattle; Chromopertubation; Laparoscopy; Tubal patency